RELEVANSI TA’ZIR SEBAGAI ALTERNATIF PEMIDANAAN DALAM SISTEM HUKUM PIDANA MODERN - Putri Aningsih, Anita; Hilda Amelia, Annisa; Asla Annisa Soleha, Putri; Syah, Rahmat; Saiin, Asrizal (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2026)
This study aims to analyze the relevance of the ta’zir concept in Islamic criminal law as a more humanistic alternative to the modern criminal justice system. The research method used is a library research with a descriptive qualitative approach through an analysis of literature, classical fiqh jinayah books, and relevant academic journals. The results show that the ta’zir concept offers high flexibility and emphasizes moral and educational aspects for offenders, contrasting with the retributive nature of modern punishment systems. Ta’zir allows judges to impose penalties based on the offender’s intent, degree of guilt, and public benefit. The discussion reveals that the implementation of ta’zir values could strengthen the national legal system by promoting substantive justice rooted in humanitarian and Pancasila values. In conclusion, integrating ta’zir principles into the modern criminal justice system can be a strategic step toward a more ethical, fair, and socially beneficial legal framework.